Evaluation of the problems of nurses caring for patients with coronavirus hospitalized in Kashan medical sciences hospitals in 2021 - Masoumeh Monemi-Bidgoli; Mohammad Afshar; Mohammad Javad Azadchehr (Fiyz̤, 2022)
Background: Covid-19 reduces the quality of service to patients with physical and emotional problems. This study aimed to determine the problems of nurses caring for patients with coronavirus hospitalized in Kashan medical sciences hospitals in 2021. Materials and Methods: The cross-sectional study was performed on 260 nurses working in Shahid Beheshti Hospital and Seyed Al-Shohada who had at least one month of care for patients with Covid-19. The researcher selected the samples and asked them to complete the questionnaire of demographic informations and problems of nurses in caring for patients with Covid-19. Then the results were analyzed using chi-square, ANOVA and Pearson correlation coefficients in SPSS 16 software. Results: The mean care of patients with Covid-19 in nurses was moderate (94.13±19.01) with frequency (51.1%). Also, the highest rate of problems was in the personal domain (22.16± 4.54) with a frequency (61.5%) and the lowest was in the motivational domain (6.20±2.98) with a frequency (38.7%). And knowledge and experience (4.93±1.74) with frequency (41.1%). The domain of physical and mental problems had a significant relationship with gender (P<0.05). The domain of personal problems was significantly related to the type of hospital and the number of children (P<0.05), also. Conclusion: The results of the study showed that rate of nurses' problems in caring for patients with Covid-19 is moderate. Therefore, it is suggested that hospital managers should make the necessary plans to solve the problems of nurses.